2020
DOI: 10.3390/agriculture10070306
|View full text |Cite
|
Sign up to set email alerts
|

Gliricidia Agroforestry Technology Adoption Potential in Selected Dryland Areas of Dodoma Region, Tanzania

Abstract: Declining soil fertility is one of the major problems facing producers of field crops in most dryland areas of Sub-Saharan Africa. In response to the declining soil fertility, extensive participatory research has been undertaken by the World Agroforestry (ICRAF) and smallholder farmers in Dodoma region, Tanzania. The research has, amongst others, led to the development of Gliricidia agroforestry technology. The positive impact of Gliricidia intercropping on crop yields has been established. However, informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
(101 reference statements)
0
10
0
Order By: Relevance
“…The theory on diffusion of innovation was relevant as Gliricidia agroforestry intercropping is a new technology that can spread within the community. Feder et al [60], Rogers [61], Kadigi et al [8], and Swamila et al [4] argue that individual farmers' adoption of improved agricultural technologies in a long-run equilibrium depends on access to full information about relative advantages. According to [45,62], a relative advantage of this technology compared to others is its short (≤5 years) and long-term (>10 years) profitability.…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…The theory on diffusion of innovation was relevant as Gliricidia agroforestry intercropping is a new technology that can spread within the community. Feder et al [60], Rogers [61], Kadigi et al [8], and Swamila et al [4] argue that individual farmers' adoption of improved agricultural technologies in a long-run equilibrium depends on access to full information about relative advantages. According to [45,62], a relative advantage of this technology compared to others is its short (≤5 years) and long-term (>10 years) profitability.…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
“…The sustainable productivity of field crops such as cereals and pulses in most dryland areas of sub-Saharan Africa (SSA) is limited by declining soil fertility and high vulnerability to weather and natural disasters [1][2][3][4]. Most cereal food crops such as maize are produced under low nitrogen (N) and phosphorous (P) conditions that have contributed to the yield gap of between 200% and 300% [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings highlight the challenge of adopting impactful adaptative practices in the context climate variability, when practices that achieve both productivity and resilience outcomes under conditions of natural water scarcity (drought) underperform in other conditions. Another study, which modeled Gliricidia agroforestry adoption rates, showed complex findings (Swamila et al, 2020). On one hand, the perceived climate and economic resilience benefits of Gliricidia agroforestry were considered a motivating factor in predicting adoption rates of the practice by smallholder farmers.…”
Section: Productivity Resilience and Mitigationmentioning
confidence: 99%